Struktur dan Sifat Mekanik Film Bacterial Cellulose dengan Disintegrasi Mekanis - Muhamad Muhajir; Heru Suryanto; Aisyah Larasati (Universitas Negeri Malang, 2018)
Film structure was greatly affected to mechanical properties of Bacterial Cellulose (BC). An engineering effort on Bacterial Cellulose Fibers (BCF) structure was changing the size and distribution of BC fiber through mechanical disintegrator process using a High Speed Blender (HSB). This study aimed to show the effect of disintegrator to the structure and mechanical properties of BCF film. The method used in this study is a synthesis of BCF from fermentation from pineapple peel waste with incubation of Acetobacter xylinum (A. xylinum) for 14 days. BC pellicle was soaked by using 1% NaOH for 24 hours then distrusted using the HSB with code speed variation of L (18000 rpm), M (21000 rpm), and H (26000 rpm) for 5 min. Then film formed by a casting method and dried in the oven at a temperature of 60 °C for 8 hours. The study result showed that the morphology of BCF formed pores, the crystallinity decreased so the tensile strength was decreased by 94%. The results of this study are expected to provide engineering information on the BCF structure potentially for filters and for sensors. DOI: http://dx.doi.org/10.17977/um024v3i22018p055